Good Arabs : The Israeli Security Agencies and the Israeli Arabs, 1948-1967 - Cohen, Hillel (Book collections on Project MUSE., 2010)
Covering a broad spectrum of attitudes and behaviours, this book brings together the stories of activists, mukhtars collaborators, teachers, and sheikhs, telling how Israeli security agencies penetrated Arab communities, how they obtained collaboration, and how activists fought them.